Micronekton diel vertical migration and active flux in the subtropical Northeast Atlantic - Vicente Ariza,Alejandro (2017)
Programa de doctorado: Oceanografía Diel Vertical Migration (DVM) is the most important synchronized animal movement in the ocean, and probably represents the largest migration on the planet in terms of biomass. The most extensive vertical displacements (hundreds of meters) are mainly undertaken by large zooplankton, as well as by small sh, shrimp and squid commonly known as micronekton. By feeding at the surface and then moving back to the deep, migrants play a key role in transferring energy and organic matter from productive shallow waters to the deep ocean. In this way, the atmospheric carbon incorporated into shallowliving organisms is exported to deeper waters and thus a ecting the global carbon cycle. Despite their importance, the micronekton have been systematically neglected by those developing biogeochemical budgets for the ocean. In this thesis we study micronekton vertical migration and its contribution to carbon export at the Canary Islands (subtropical northeast Atlantic). Since vertical migration can be monitored acoustically using echosounders, we rst described the main organisms causing sound scattering in the region. We have identi ed diverse animal layers and migrations extending down to at least 800 m depth according to acoustic records and net sampling. Migrant biomass estimates and respiration rates also demonstrate that micronekton are as e cient as zooplankton in storing carbon in intermediate waters (200-1000 m depth), with sh being the most important group. We also found that vertical distribution and migrant behavior changes drastically during light attenuation and pollution episodes associated with a submarine volcano eruption. The horizontal distribution of the micronekton was likewise a ected by oceanic eddies, which introduced a high degree of patchiness in animals inhabiting down to 900 m depth. We further discuss the potential contribution of micronekton to sequestering of carbon beyond 1000 m depth, based on their extensive migrations and physiological features. Our results ...